2020
DOI: 10.21203/rs.3.rs-52544/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization of florfenicol resistance genes in the coagulase-negative Staphylococcus  (CoNS) isolates and genomic features of  a  multidrug-resistant Staphylococcus lentus strain H29

Abstract: BackgroundWith the wide use of florfenicol to prevent and treat the bacterial infection of domestic animals, the emergence of the florfenicol resistance bacteria is increasingly serious. It is very important to elucidate the molecular mechanism of the bacteria’s resistance to florfenicol. MethodsThe minimum inhibitory concentration (MIC) levels was determined by the agar dilution method, and polymerase chain reaction (PCR) was conducted to analyze the distribution of florfenicol resistance genes in 39 CoNS str… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
(20 reference statements)
0
0
0
Order By: Relevance
“…Previously, Qian et al (2015) reported that blactam antimicrobial agents such as penicillin, cephalosporin, and monobactams were extensively used for the treatment of bovine mastitis caused by Staphylococcus species. Among the amphenicol ARGs, only the floR gene was harbored by S. haemolyticus strains, which is in accordance with the previously published study by Wu et al (2021). Florfenicol is one of the most commonly used antimicrobials in the dairy sector because of its wide range of antimicrobial activity (Kawalek et al, 2016).…”
Section: St8 St3 St11 St22supporting
confidence: 88%
See 1 more Smart Citation
“…Previously, Qian et al (2015) reported that blactam antimicrobial agents such as penicillin, cephalosporin, and monobactams were extensively used for the treatment of bovine mastitis caused by Staphylococcus species. Among the amphenicol ARGs, only the floR gene was harbored by S. haemolyticus strains, which is in accordance with the previously published study by Wu et al (2021). Florfenicol is one of the most commonly used antimicrobials in the dairy sector because of its wide range of antimicrobial activity (Kawalek et al, 2016).…”
Section: St8 St3 St11 St22supporting
confidence: 88%
“…NAS is one of the most important and widespread groups of pathogens including numerous species such as S. chromogenes, S. haemolyticus, S. sciuri, S. saprophyticus, S. simulans, S. succinus, and S. epidermidis (Wald et al, 2019). NAS pathogens are not only opportunistic in animals and humans but are also widely distributed in the environment such as dust, soil, water, and air (Wu et al, 2021). Although NAS species are considered to be a pathogen of low clinical incidence, it has recently been identified as the relatively common causative agent of bovine mastitis in many countries including China (Al-Harbi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%